ANALISIS MINAT DAN MOTIVASI MAHASISWA PENDIDIKAN JASMANI TERHADAP PARTISIPASI DALAM KLUB SEPAK TAKRAW DI TIMOR-LESTE: MINAT DAN MOTIVASI MAHASISWA PENDIDIKAN JASMANI, KLUB SEPAK TAKRAW DI TIMOR-LESTE - Filomeno Amaral Bria (Universitas Hamzanwadi, 2026)
Student participation in sepak takraw clubs in Timor-Leste still varies, influenced by psychological factors such as interest and motivation. This study aims to analyze the level of interest and motivation among students regarding participation in sepak takraw clubs in Timor-Leste. The study employs a quantitative approach using a descriptive survey method. The sample consisted of 150 students selected through purposive sampling based on the following criteria: having passed the sepak takraw course, being selected in the team entrance test, and having attended at least 3 training sessions in the past 6 months. The instrument was a 30-item Likert scale questionnaire that had been tested for validity and reliability (Cronbach’s Alpha = 0.87). Data analysis used descriptive statistics. The results of the study indicate that student interest falls into the high category (76.4%), intrinsic motivation into the very high category (81.6%), and extrinsic motivation into the high category (74.2%). Intrinsic motivation is the most dominant factor in driving student participation. This study concludes that students’ interest and motivation toward the sepak takraw club are relatively high, with intrinsic motivation as the primary factor. However, extrinsic motivation still needs to be enhanced through regular competitions and a reward system. The study was conducted at only one campus and did not measure environmental factors such as facilities.